Condom Accessibility: The Moderating Effects of Alcohol Use and Erotophobia in the Information–Motivation–Behavioral Skills Model. Issue 5 (September 2013) - Harkabus, Lindsey C.; Harman, Jennifer J.; Puntenney, Jamie M.
Objective . The information–motivation–behavioral skills model was used to investigate which factors were associated with condom accessibility among undergraduate college aged adults. Our aim was to also examine moderating effects of erotophobia/erotophilia and alcohol use, as these have been related to sexual risk and prevention behaviors among young adults. Method . Participants completed survey questionnaires on personal computers. Results . Support was found for the paths of the information–motivation–behavioral skills model. Alcohol use moderated the mediating effect of behavioral skills between motivation and condom accessibility, and erotophobia/erotophilia moderated the effect of motivation and behavioral skills on condom accessibility. Higher alcohol use was associated with a lower likelihood of having condoms accessible, and individuals with higher levels of erotophobia had weaker paths between motivation and behavioral skills than those with lower levels. Discussion . Discussion centers on the role of individual differences on protective behaviors that require planning and how intervention efforts can be tailored to promote these changes.